Photocatalytic activity and characterization of sol-gel-derived Cr(III)-doped TiO(2)-coated active carbon composites - Gambhire, A. B.; Lande, Machhindra K.; Mandale, A. B.; Patil, K. R.; Arbad, B. R. (Philosophical Magazine, 2008)
Cr(III)-doped, TiO(2)-coated active carbon (Cr-TiO(2)/AC) were prepared by a sol-gel method. The effect of supports, including TiO(2) and active carbon (AC), on the molecular structure and photocatalytic activity of chromium oxide for complete decomposition of EDTA has been examined with respect to the content of Cr on the catalyst surface. The photocatalytic activity of the Cr-TiO(2)/AC composites was evaluated in the decomposition of EDTA solution under UV irradiation. The results indicate that Cr-TiO(2)/AC has a higher efficiency in decomposition of EDTA than TiO(2), TiO(2)/AC or active carbon. This was attributed to the different functions of active carbon and chromate species. (1) Nanosize TiO(2) particles on composites were not reunited, possible because active carbon retards transformation of anatase into rutile and decreases the crystallite size. (2) Production of high concentrations of organic compound near Cr-TiO(2). (3) Carbon in active carbon causes some of the TiO(2) to reduce to Ti(3+) ions, which prevents electron-hole pair recombination. (4) Formation of polychromate species, with a stronger redox capability, on the surface of TiO(2)/AC. It was found that the addition of Cr to TiO(2) sol could suppress the grain growth of TiO(2) crystals and increase the hydroxyl content on the surface of TiO(2)/AC. The photocatalytic efficiency and activity of the composites remained good, even after three cycles.
Keywords: EDTA; photoactive; sol-gel; Titanium dioxide; XPS